Current status and future perspective of natural killer cell therapy for cancer - Zhao Xiangyu; Lin Minghao; Huang Xiaojun (Medical Review, 2023)
Natural killer (NK) cells possess innate abilities to effectively eliminate cancer cells. However, because of difficulties of proliferation and easy to be induced dysfunction in the setting of cancer post NK cell therapy, the curative effect of NK cell infusion has been constrained and not been widely applicable in clinical practice. The rapid development of biotechnology has promoted the development of NK cell therapy for cancer treatment. In this review, we will provide a comprehensive analysis of the current status and future prospects of NK cell therapy for cancer, focusing on the biological characteristics of NK cells, as well as strategies to enhance their targeting capabilities and overcome tumor immune suppression within the microenvironment.